La via transculturale per la salute di tutti - Pisani, Salvatore (TransCulturale, 2022)
Transcultural approach, already known in medicine as a branch of psychiatry, is also used in epidemiology. Some examples, such as recent pandemic, cancer geography, health inequalities in migrants, cronic eating diseases, share contexts belonging both to transculturalism and epidemiology. The idea of illness required by transculturalism is different from a random event, and looks at common elements in the population. A further basic element is that the diseases cross national as well as ethnic and cultural bounderies. A third consideration involves ecological studies, based on the recognition of otherness for scientific progress. Finally, epidemiology deals with frail and migrant populations, detecting health inequalities and suggesting measures to fight them. These measures are prevention, regarding what comes before the disease, with involvement of doctors, educators, psycologists, sociologists.